Laser Material Interaction Modeling Using the COMSOL Multiphysics Software - Salih, Noor Ibrahim touma; Jassim, Ghufran Ali Hussein; abbas, Rafal Abbas Hasan; Al-Khazraji, Saba Ali Naeem Abed; Mansour, Zainab Salem Jabbar (American Journal of Botany and Bioengineering, 2025)
This project focuses on the modeling and simulation of LASER material interactions using the COMSOL Multiphysics software. LASER material interactions play a crucial role in various fields, including manufacturing, electronics, and medicine. The objective of this study is to develop a comprehensive understanding of the fundamental principles underlying LASER material interactions and to utilize computational modeling techniques to analyze and predict the thermal and optical responses of different materials to LASER irradiation. The project involves the development of a computational model using COMSOL Multiphysics to simulate the LASER material interactions on a silicon wafer. The model takes into account factors such as absorption, scattering, and thermal diffusion to accurately predict the temperature distribution.